O fortalecimento das dimensões da capacidade estatal dos consórcios públicos intermunicipais - Paulo Sérgio Mendes César (2021)
The thesis investigated the aspects that influence the institutional strengthening of inter-municipal public consortia regarding their capacity to implement public policies. The theme of this research is inserted in the field of study of intergovernmental relations and public policies, which is part of the research line State, Management and Public Policies in the Graduate Program in Political Science at UFMG. Considering the difficulty of a large portion of Brazilian municipalities to implement public policies, which in a way has fostered the expansion of the number of consortia in various areas of activity, as well as the scarcity of empirical studies on the subject, this work will examine the main aspects potentially related to the improvement of the institutional capacity of the consortia regarding public policies. Thus, the questions that guided the research were: If regional governance can rationalize the formulation of public policies and generate economies of scale, consequently increasing the efficiency of public policy, why are public consortia not always strengthened? And why, in some regions where there are many strengthened consortia, others aren't? And in the same way, why in contexts where it is natural for consortia not to be strengthened, do some end up standing out? Therefore, using, at first, the literature on Brazilian federalism, its historical evolution, its main characteristics and contextualization of intergovernmental cooperation, we continued with the study of municipalities, also addressing their historical background to recognition as a federative entity by the Federal Constitution of 1988. Regarding the municipalities, aspects related to their administrative competences, the heterogeneity found in the country, as well as the fiscal aspects of the municipalities in relation to our federative pact were also presented. Considering the object of the study, linked to the success of intermunicipal cooperation, it was essential to bring to the discussion a rich but objective discussion on regional governance, which starts from the Theory of Rational Choice and Collective Action, reaching the costs encapsulated in regional governance and the dilemma between local and regional action. Still on the literature review, we started to investigate the figure of public consortia itself, their trajectory in our country until the current configuration, current advantages and challenges, as well as the dimensions of institutional capacity that are relevant to them. To answer the research questions, the study adopted two research stages. The first stage, quantitative, with several descriptive and analytical statistical manipulations of municipal financial data made available by the Secretaria do Tesouro National (STN) from 2007 to 2018. Not only allowing different signals about the municipal financing of consortia, a variable considered in the first stage of the research to understand the institutional strengthening of public consortia, the quantitative stage also provided for the grouping and classification of the 5,570 Brazilian municipalities into clusters. At each stage of creation of new clusters and subclusters, the most similar groups were merged, considering the context of municipal transfers to consortia for each state, the average gross domestic product of the states and an index combining the information from the variables about revenues and municipal expenses. At each stage of creation of new clusters and subclusters, the most similar groups were merged, considering the context of municipal transfers to consortia for each state, the average Gross Domestic Product (GDP) of the states and an index combining the information from the variables about revenues and municipal expenses. Following the case study methodology, in the second stage, four consortia were selected to verify the influence of qualitative variables, two with extreme scenarios for financing consortia within the cluster with better context and two with extreme scenarios for financing consortia within the cluster with worse context found in the first stage. Documentary analysis and semi-structured interviews were carried out with representatives of the selected consortia in order to better explain the results indicated in this stage. The survey results point to a general improvement in the financial capacity of consortia over time, with an increase in the number of municipalities financing consortia and an increase in the volumes transferred between 2007 and 2018. Despite the prioritization of consortia being a natural expectation for municipalities with less financial resources available to implement their public policies in isolation, the pattern was found that municipalities that finance consortia on average have more financial resources, that is, municipalities that do not consortium have lower average revenues. Furthermore, the statistical correlations between municipal financial data proved to be valid. The volume of resources transferred to consortia highlights Paraná, the largest consortium funder in the period analyzed. In the cluster analysis, extreme contexts were identified between the cluster in the North and Northeast regions in the worst scenario and with the one in the State of Paraná as the best scenario. Within the North and Northeast cluster extreme scenarios were found in the states of Ceará and Pará, and in the Paraná cluster the extremes are between the Northwest and South of the state. Thus, in a complementary way, seeking to deepen the quantitative findings, case studies were carried out in four public consortia selected through this cluster analysis. Cases that pointed out states, public policies and mayors as conditioning factors to capacity building. However, the highlighted relevance of public policy and state support for consortia was observed, especially when it comes to more complex public policies such as health. Roughly speaking, the cases allowed us to conclude that public consortia with greater financial capacity also tend to have greater bureaucratic, legislative and infrastructure capacity.